2015
DOI: 10.1073/pnas.1521316112
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of arsenic-binding proteins reveals that hexokinase-2 is inhibited by arsenic

Abstract: Arsenic is highly effective for treating acute promyelocytic leukemia (APL) and has shown significant promise against many other tumors. However, although its mechanistic effects in APL are established, its broader anticancer mode of action is not understood. In this study, using a human proteome microarray, we identified 360 proteins that specifically bind arsenic. Among the most highly enriched proteins in this set are those in the glycolysis pathway, including the rate-limiting enzyme in glycolysis, hexokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 33 publications
2
101
0
Order By: Relevance
“…But, as demonstrated by a variety of other studies, cell lines of solid tumors were usually treated with 1-2 μM ATO for 12-24 h, and significant growth inhibition and apoptosis were observed in many of these cell lines, such as MGC803 [39], MCF-7, HeLa, and HIC [40]. According to our recent study [38], significant growth inhibition was also observed in SGC7901 cells after 12-24 h of ATO treatment at a dose of 2 μM. Our study employing the human protein microarray showed that ATO-binding proteins are involved in a variety of cellular signaling pathway, such as apoptosis, protein kinase, and acetylation/deacetylation pathway.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…But, as demonstrated by a variety of other studies, cell lines of solid tumors were usually treated with 1-2 μM ATO for 12-24 h, and significant growth inhibition and apoptosis were observed in many of these cell lines, such as MGC803 [39], MCF-7, HeLa, and HIC [40]. According to our recent study [38], significant growth inhibition was also observed in SGC7901 cells after 12-24 h of ATO treatment at a dose of 2 μM. Our study employing the human protein microarray showed that ATO-binding proteins are involved in a variety of cellular signaling pathway, such as apoptosis, protein kinase, and acetylation/deacetylation pathway.…”
Section: Discussionmentioning
confidence: 88%
“…As such, we could then correlate the metabolomics data with transcriptomics and proteomics. This multiple level investigation would definitely help us to understand MOA of ATO at a more systematical and comprehensive level [38].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, analysing the CTD results, the identified compounds have to be subdivided between toxic and therapeutic because the database structure does not provide for a subdivision a priori. On this basis, one of the most interesting compounds was 4-aminophenylarsenoxide, an arsenic derivative, already used as a chemotherapeutic together with imatinib in the treatment of chronic myeloid leukaemia, that has been used alone with some success to treat multiple myeloma, myelodysplasia syndrome and non-Hodgkin’s lymphoma 33. Another intriguing compound was PD 0325901, a second-generation MEK inhibitor, currently in phase I trial for treating patients with solid tumours that have spread to other parts of the body or cannot be removed by surgery (National Cancer Institute, https://www.cancer.gov).…”
Section: Discussionmentioning
confidence: 99%